The Analysis of Carbon Credit Monetization in the Mining & Energy Company - Demario, Patrick; Nainggolan, Yunieta Anny (Journal Integration of Management Studies, 2025)
This study examines the recently launched Indonesian carbon market, IDX Carbon, with a focus on its applicability to publicly listed mining and energy companies. The research compares IDX Carbon with established carbon trading systems in the European Union and China to assess structural differences and pricing mechanisms. Using emissions data from 2020 to 2023, the study calculates annual emission surpluses and deficits based on Phase 1 carbon accounting. Findings reveal that most Indonesian companies are in a carbon credit deficit, resulting in added operational costs. Although the potential for monetizing carbon credits exists, particularly for companies with emission surpluses, the overall financial benefit remains limited under current market conditions. Notably, the price per ton of CO₂e in Indonesia is significantly lower than in the EU and China, indicating that the Indonesian carbon market is still undervalued and lacks liquidity. These conditions may discourage active participation and weaken the market’s role in driving corporate decarbonization. This research contributes to the understanding of early-stage carbon market implementation in developing economies and highlights areas for improvement in regulatory design, carbon pricing, and reporting transparency. It also provides a basis for future studies on sustainable finance and carbon policy reform in Indonesia, especially in high-emission sectors like mining and energy.